Five-Year Experience with Screening Electrocardiograms in National Collegiate Athletic Association Division I Athletes. Issue 5 (September 2016) - Fuller, Colin; Scott, Carol; Hug-English, Cheryl; Yang, Wei; Pasternak, Andrew
Abstract : Objective: (1) Compare rates of abnormal screening electrocardiograms (ECGs) using updated criteria compared with older criteria. (2) Compare rates of abnormal ECGs by ethnicity. (3) Evaluate ability of ECG criteria to detect the predicted number of athletes with previously undetected cardiovascular abnormalities. Design: Prospective and retrospective review of ECGs. During the prospective portion of the study, the 2005 European Society of Cardiology criteria were used from 2008 to July 2011 and the 2011 Stanford criteria were used from August 2011 to 2013. Retrospectively, all ECGs were reevaluated using the 2011 Stanford criteria, 2013 Seattle criteria, and 2014 Sharma Refined criteria. Setting: Division I National Collegiate Athletic Association University. Participants: 874 incoming athletes over a 5-year period. Interventions: ECG screening program. Main Outcome Measures: Number of abnormal ECGs and number of athletes with newly discovered cardiac abnormalities. Results: Abnormal ECG rates were the 2005 European criteria 10.7%, 2011 Stanford criteria 6.6%, 2013 Seattle criteria 2.8%, and 2014 Sharma Refined criteria 2.8%. In black athletes, the Stanford criteria resulted in more abnormal ECGs compared with Seattle or Sharma Refined. Three athletes were found to have a previously undetected cardiac abnormality (2 with hypertrophic cardiomyopathy and 1 with preexcitation). Conclusions: More recent ECG screening criteria substantially reduce the abnormal ECG rate and thus the number of athletes requiring additional testing. ECG screening criteria identified the predicted number (1/300) of young athletes with serious underlying cardiovascular disease. These criteria prompt not only additional cardiovascular testing but also a more thorough cardiovascular history.